Evaluation of matrix-induced autologous chondrocyte implantation in combination with high tibial osteotomy: A prospective study. Issue 5 (31st May 2019) - Parker, David A; Giuffre, Bruno; Macpherson, Gavin; Coolican, Myles RJ; Neri, Thomas
Objectives: Matrix Induced Autologous Chondrocyte Implantation (MACI) has been reported to be an effective treatment for symptomatic cartilage defects with many studies finding improvements in pain and function. MACI in combination with HTO in the surgical management of varus malalignment with knee medial compartment cartilage loss improves clinical and MRI results beyond HTO alone. Methods: Twenty nine patients (n=31 knees) fulfilling HTO surgery inclusion criteria were prospectively enrolled and analysed in two groups: MACI+HTO (n=14); HTO-only (n=17). After a 12-months follow-up period, clinical scores (IKDC, KOOS and WOMAC) and Magnetic Resonance Imaging (MRI) assessment were analysed. MRI was firstly performed to evaluate the semi-quantitative Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) score. Delayed Gadolinium Enhanced MRI of cartilage (dGEMRIC) protocol measuring T1Gd relaxation times was then use to assess the regenerated cartilage quality. Results: While significant improvement in clinical scores was found in both groups, the MACI+HTO group only demonstrated greater improvement in the symptoms sub-scale of KOOS (p<0.05) compared to the HTO-only group (p=0.016). The mean MOCART scores of the MACI+HTO patients was 34.6±14.8 [15-70] and a complete cartilage defect filling was confirmed in only 14.3% (n=2). Analysis of dGEMRIC images revealed no significant differences and a high between-subject variability in change of dGEMRIC indices across the follow-up period between groups. Conclusion: All knees, regardless of treatment, had significant clinical improvements at one-year post surgery. MACI may have additional clinical benefit in self-reported symptoms in the short term. Clinical improvements in patient scores are not explained by MRI findings that showed a poor structure of the repaired tissue in the majority of cases, and are most likely related solely to the HTO. Combined MACI+HTO had additional questionable clinical benefit in self-reported symptoms for patients with varus malalignment and knee medial compartment OA. For orthopaedic surgeons who may be contemplating this procedure, the additional cost and morbidities associated with the MACI graft is not justified.